Can Physical Activity Patterns before and during Pregnancy and Anxiety be Related to Preterm Birth? - Pourahmad , Zohreh; Namavar Jahromi , Bahia; Koushkie Jahromi, Maryam (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Changes of physical activity before and during three trimesters of pregnancy known as pattern of physical activity and anxiety during pregnancy can be two concerns of pregnant women about preterm birth which require clarification. So, this retrospective study aimed to assess the effect of pattern of physical activity, and anxiety on preterm birth in Iranian pregnant women. Methods: This study was a kind of descriptive correlation which was performed retrospectively. Participants of this study (2019-2020) included 118 pregnant women with preterm (n=62) and term (n=56) birth who participated in the study voluntarily and were selected according to the study inclusion criteria. The energy cost of physical activity before and during three trimesters of pregnancy, and anxiety level were recorded through interview using pregnancy physical activity (PPAQ) and Hospital Anxiety and Depression Rating Scale Anxiety (HADS) questionnaires respectively. Results: There was no significant difference between preterm and term birth groups regarding total physical activity, and sedentary behavior energy expenditure before and during pregnancy as well as anxiety during pregnancy(P>0.05). Physical activity pattern was not significantly different between the two groups (P>0.05). However, physical activity before pregnancy was significantly higher than all trimesters of pregnancy in both groups of the study (P<0.001). In two groups of preterm and term deliver, physical activity reduced in the third compared to the second trimester of pregnancy similarly. Conclusions: Physical activity reduced during pregnancy in preterm and term birth women similarly. In this study, physical activity, sedentary behavior and anxiety during pregnancy and before it were not effective on the pre-term birth.